Water mass circulation and weathering inputs in the Labrador Sea based on coupled Hf–Nd isotope compositions and rare earth element distributions. (15th February 2017) - Filippova, Alexandra; Frank, Martin; Kienast, Markus; Rickli, Jörg; Hathorne, Ed; Yashayaev, Igor M.; Pahnke, Katharina
Abstract: The Labrador Sea is one of the key areas for deep water formation driving the Atlantic thermohaline circulation and thus plays an important role in Northern Hemisphere climatic fluctuations. In order to better constrain the overturning processes and the origins of the distinct water masses, combined dissolved Hf–Nd isotopic compositions and rare earth element (REE) distribution patterns were obtained from four water depth profiles along a section across the Labrador Sea. These were complemented by one surface sample off the southern tip of Greenland, three shallow water samples off the coast of Newfoundland, and two deep water samples off Nova Scotia. Although light REEs are markedly enriched in the surface waters off the coast of Newfoundland compared to north Atlantic waters, the REE concentration profiles are essentially invariant throughout the water column across the Labrador Sea. The hafnium concentrations of surface waters exhibit a narrow range between 0.6 and 1 pmol/kg but are not significantly higher than at depth. Neodymium isotope signatures (ɛNd) vary from unradiogenic values between −16.8 and −14.9 at the surface to more radiogenic values near −11.0 at the bottom of the Labrador Sea mainly reflecting the advection of the Denmark Strait Overflow Water and North East Atlantic Deep Water, the signatures of which are influenced by weathering contributions from Icelandic basalts. Unlike Nd, water column radiogenic Hf isotope signatures (ɛHf) are more variable representing diverse weathering inputs from the surrounding landmasses. The least radiogenic seawater ɛHf signatures (up to −11.7) are found in surface waters close to Greenland and near the Canadian margin. This reflects the influence of recirculating Irminger Current Waters, which are affected by highly unradiogenic inputs from Greenland. A three to four ɛHf unit difference is observed between Denmark Strait Overflow Water (ɛHf ∼ −4) and North East Atlantic Deep Water (ɛHf ∼ −0.1), although their source waters have essentially the same ɛNd signature. This most likely reflects different weathering signals of hafnium delivered to Denmark Strait Overflow Water and North East Atlantic Deep Water (incongruent weathering of old rocks from Greenland versus basaltic rocks from Iceland). In addition, the ɛHf data resolve two layers within the main body of Labrador Sea Water not visible in the ɛNd distribution, which are shallow Labrador Sea Water (ɛHf ∼ −2) and deep Labrador Sea Water (ɛHf ∼ −4.5). The latter layer was formed between the late 1980's and mid 1990's during the last cold state of the Labrador Sea and underwent substantial modification since its formation through the admixture of Irminger Water, Iceland Slope Water and North East Atlantic Deep Water, which is reflected in its less radiogenic ɛHf signature. The overall behavior of Hf in the water column suggests its higher sensitivity to local changes in weathering inputs on annual to decadal timescales. Although application of Hf isotopes as a tracer for global water mass mixing is complicated by their susceptibility to incongruent weathering inputs they are a promising tracer of local processes in restricted basins such as the Labrador Sea.